Cultural and Digital Integration: Revitalization Strategy For Sumbawa Horse Racing As A Sustainable Tourism Destination at Angin Laut Biru Arena: Integrasi Budaya dan Digital: Strategi Revitalisasi Pacuan Kuda Sumbawa sebagai Destinasi Pariwisata Berkelanjutan di Arena Angin Laut Biru - Hadi, Firno; Mansyur, Abdurrahman (RADIANT: Journal of Applied, Social, and Education Studies, 2026)
This study examines a critical intervention in revitalizing intangible cultural heritage through digital symbiosis, focusing on the Sumbawa traditional horse race (Bare Spee) at Angin Laut Biru Arena. As a living embodiment of indigenous values including honor (siri'), communal solidarity (menyama braya), and ethno-ecological wisdom, this tradition faces erosion due to generational disconnect, infrastructural neglect, and rigid management practices. Addressing the lack of integrated digital and cultural frameworks for rural heritage, the study employs an immersive qualitative case study approach. Data were triangulated through participatory observation across two event cycles, in-depth interviews with 22 key stakeholders consisting of ritual elders, kebalan jockeys, samara horse masters, local entrepreneurs, and cultural tourists, as well as digital ethnography. The findings identify a tripartite authenticity framework comprising ritual sanctity, socio-familial reciprocity, and embodied equine knowledge. Based on this analysis, the study proposes a Symbiotic Digital Mediation Model implemented through four strategies, namely community-curated digital storytelling by local youth, context-aware augmented reality using QR-based cultural portals with native-language narratives, an integrated digital ecosystem encompassing a heritage portal, blockchain-based ticketing, and a local product e-marketplace, and the use of appropriate lightweight digital tools for event management and documentation. Crucially, the study demonstrates that digital mediation must adhere to cultural subsidiarity so that technology amplifies rather than replaces indigenous epistemologies. The model supports regenerative cultural governance by enabling community-led digital stewardship and offers broader implications for safeguarding living heritage in the digital era.